Ayni: An experience of collective occupations as a response to the COVID-19 pandemic in Santa Clara del Mar, Argentina in the year 2020 - Arraras, Daniel Matías; Cabrera, Marina Cecilia; Brescia, Catalina (Groupwork, 2025)
This article reflects on the contribution of collective occupations to social transformation processes in a small town in Buenos Aires Province: Santa Clara del Mar, Argentina. On March 20, 2020, imposed a lockdown which, among other things, required people to stay at home. In response, a group of residents came together to carry out community activities with the aim of providing assistance and support to the most vulnerable people in the community. This group of people called themselves ‘Ayni’, after some Andean communities, emphasizing reciprocity. This article describes the community organization that emerged among this group of residents. It explores the individual and collective transformations that arose, seeking to construct knowledge based on the logic of social actors. A qualitative research methodology used for data collection was structured, using the techniques of participant observation and in-depth interviews. Other data sources used included a WhatsApp group and written records of ‘Ayni’ meetings. As part of the main conclusions. This work highlights the value attributed to collective occupations as a possibility for building community networks in people’s daily lives.